SG-APSIC1122: Observational study of handwashing sink activities in the inpatient setting - Xiaowei Huan; Sharifah Farhanah; Kyaw Zaw Linn; Clara Chong Hui Ong; Liang Hui Loo; Allie Yin Lim; Nur Hafizah Binte Hamad; Chu Ying Poon; Hui Ru Tan; Ying Wei Tang; Brenda Sze Peng Ang; Marimuthu Kalisvar (Cambridge University Press, 2023)
Objectives: The use of handwashing sinks for activities other than hand hygiene (HH) is associated with higher rates of β-lactamase-producing Enterobacteriaceae. However, little has been published about the handwashing sink activities in Singapore hospitals. We explored the handwashing sink activities in a tertiary-care hospital in Singapore. Methods: Five trained shadow observers conducted this observational study between December 18 and 21, 2018 (6 hours per day: 07:00-09:00, 09:30-11:30, and 12:30-14:30) in acute-care general wards. We divided the handwashing sink activities by healthcare workers (HCWs) and non-HCWs (ie, visitors, caregivers, and relatives) and by HH- and non-HH-related activities. We used Stata version 15 software for the analysis. The study was approved by the Institutional Review Board of the National Healthcare Group, Singapore (DSRB no. 2020/01257). Results: In total, 657 handwashing sink activities were recorded [HCWs, 475 (72.3%) and non-HCWs, 182 (27.7%)]. Of the 475 HCW handwashing sink activities, 451 (94.9%) were HH-related, 10 (2.1%) were for patient nutrition, 7 (1.5%) were for environmental care, 6 (1.3%) were for medical equipment cleaning, and 1 (0.2%) was patient personal-item cleaning. Of the 182 handwashing sink activities by non-HCWs, 117 (64.3%) were HH related, 30 (16.5%) were for patient nutrition, 21 (11.5%) were for personal hygiene, 14 (7.7%) were patient personal-item cleaning. The distribution of handwashing sink activities differed significantly (P < .01) between HCWs and non-HCWs. The odds of non-HH-related handwashing sink activities among non-HCWs was 10× higher than among HCWs (OR, 10.44; 95% CI, 5.98-18.23; P < .01). Conclusions: Handwashing sinks use for non-HH-related activities is higher among non-HCWs than HCWs. Further studies are needed to understand the impact of non-HH handwashing sink activities on nosocomial infections and ways to reduce them.